The Arabidopsis phenylalanine insensitive growth Mutant Exhibits a Deregulated Amino Acid Metabolism - Voll, Lars M. (American Society of Plant Biologists, 2004)
Amino acids and amino acid analogs have been used in numerous genetic screens to isolate mutants deficient in amino acid biosynthetic pathways or in the regulation of amino acid metabolism. Several of these mutants exhibit relaxed feedback control of branched amino acid biosynthetic pathways and are thus resistant to accumulation of pathway end products. For example, feedback-regulated enzymes of the shikimate pathway are anthranilate synthase on the branch leading to Trp and chorismate mutase on the branch leading to Phe and Tyr. A feedback-insensitive mutant of anthranilate synthase α, trp5-1, is resistant to toxic Trp analogs. Mutants resistant to Phe have not previously been reported, and this article describes the isolation of the recessive Arabidopsis Phe insensitive growth mutant pig1-1 by a forward genetic screen. pig1-1 was not only tolerant to Phe, Tyr, and Trp, but also to other, not biosynthetically related amino acids. Amino acid contents in pig1-1 were significantly elevated with respect to wild-type controls but, in contrast to the wild type, dramatically decreased when plants were supplemented with 2 mm Phe. Protein contents were similar in the mutant and the wild type at all tested conditions. Phe catabolism was similar to the wild type in pig1-1 roots but was significantly increased in pig1-1 shoots. Phenylalanine uptake into the root, its root-to-shoot translocation, and Phe and phenylpropanoid contents were unaltered in pig1-1, indicating that pig1-1 is not affected in amino acid translocation or the shikimate pathway. Instead, the response of pig1-1 toward amino acid feeding indicates that amino acid metabolism is generally deregulated in pig1-1.